Access security system in University Tun Hussein Onn Malaysia (Pagoh Campus) - Mariah, Awang; Ina Syazwani, Hamzah; M. A. A., Rahman; Mohd Kamaruzaman, Musa; M. M., Syafiq Syazwan; Fatimah, Yusuf; Nuramidah, Hamidon; Mohd Shahril, Abdul Rahman; Wilson Rangga, Anthony Jiram (AIP Publishing, 2021)
The study of access security system in University Tun Hussein Onn Malaysia (UTHM) in Pagoh branch is literally a research that enclosed to the safety research that involves in the entrance of the buildings to avoid any threats upcoming that can contribute to the loss of property and economic part. University is the place that involves in strong protection of security guided and commonly we all know that this system works 24 hours per day. Thus, we will be found out in this study on how the access security system is working on the campus and what are the implements that they want to obtain from working out this system. The objectives of this project are to determine the type of access security system in UTHM Pagoh campus and to study the user’s awareness about the access security system in UTHM Pagoh campus. This research study is completed by applying qualitative of research method to achieve the first objective and using quantitative method which is this project will use the questionnaire to complete and achieve the second objective. These data are then analyzed to exploit with the Statistical Package for Social Science (SPSS) version 19 and Microsoft Excel software. The data will be processed and presented in the form of chart and percentage by using this software. Last but not least, this project will find out the types of access security system available in the campus and to figure the user’s awareness of the access security in UTHM Pagoh campus.